INTRODUCTION: Developing Heuristics for Web Communication: An Introduction to This Special Issue - VAN DER GEEST, THEA and SPYRIDAKIS, JAN H. (Technical Communication, 2000)
◆ Describes the role of heuristics in the Web design and evaluation processes ◆ Explains how the heuristics in this issue were developed
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80Mzc0ODg4MQ